2020
DOI: 10.1007/s10389-020-01325-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenon of depression and anxiety related to precautions for prevention among population during the outbreak of COVID-19 in Kurdistan Region of Iraq: based on questionnaire survey

Abstract: Purpose Since December 2019, the coronavirus disease 2019 (COVID-19) epidemic has swept the world, causing widespread burden and increasingly hospitalizations. Researchers from around the world have tried to study the virus and its effect with more precision in various fields. The purpose of this study is to identify levels of anxiety and depression with regard to precautionary for prevention of COVID-19, and to identify the relationship between demographic variables and both depression and anxiety. Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
(10 reference statements)
6
16
1
Order By: Relevance
“…Hence, fear or worry about infection has strong existence among the members of the Jordanian society, regardless of their social status. This result came consistent with the study (Blbas, et al,2020;Vahedian-Azimi, et al,2020). Yet it doesn't conform with the study (Doshi, et al, 2020).…”
Section: )supporting
confidence: 93%
“…Hence, fear or worry about infection has strong existence among the members of the Jordanian society, regardless of their social status. This result came consistent with the study (Blbas, et al,2020;Vahedian-Azimi, et al,2020). Yet it doesn't conform with the study (Doshi, et al, 2020).…”
Section: )supporting
confidence: 93%
“…It is well documented that females are more likely than males to develop anxiety disorder [26]. Most studies on the general public reported higher anxiety and psychological impact in females than males during the COVID-19 pandemic [27][28], including a study in Malaysia [30]. Likewise, in this study, while gender is not a signi cant predictor of anxiety, the structural model indicated that being female is signi cantly associated with higher depression.…”
Section: Discussionsupporting
confidence: 38%
“…Ideally, sample sizes between categories are balanced for sex-and gender-sensitive comparisons in order to assure enough power or avoid bias. In 18 studies (Al Banna et al, 2020;Alonzi et al, 2020;Antunes et al, 2020;Blbas, Aziz, Nejad, & Barzinjy, 2020;Capraro & Barcelo, 2020;Civantos et al, 2020;Guo et al, 2020;Khanna, Honavar, Metla, Bhattacharya, & Maulik, 2020; Lee, Mathis, Jobe, Systematic Review: Sex-and gender-sensitive research on mental health during COVID-19 & Pappalardo, 2020;Madani, Boutebal, & Bryant, 2020;Olaseni, Oguntayo, Agberotimi, & Akinsola, 2020;Olcaysoy Okten et al, 2020;Ɩzdin & Bayrak Ɩzdin, 2020;Pillay et al, 2020;Varshney et al, 2020;Verma & Mishra, 2020;Zhuo, Gao, Wang, Zhang, & Wang, 2020) there was a predominance of male participants. Furthermore, one study reported an equal amount of male and female participants (Balkhi, Nasir, Zehra, & Riaz, 2020) and for one study, numbers of male and female participants were not presented .…”
Section: Resultsmentioning
confidence: 99%